Experiences and Perceptions of Cervical Cancer Screening Using Self-Sampling among Under-Screened Women in Flanders - Buelens, Charlotte; Stabel, Margot; Wildiers, Alice; Peremans, Lieve; Van Hal, Guido; Van Doorsselaere, Lotje; Lievens, Annouk; Vorsters, Alex; Van Keer, Severien; Verhoeven, Veronique (Healthcare (Basel), 2024)
Primary Human Papillomavirus (HPV) screening on samples collected by women themselves has proven to be an effective strategy for cervical cancer screening (CCS) and may increase participation rates in women who do not partake (regularly) in screening. The aim of this study is to investigate reasons for non-participation and perceptions of CCS using self-sampling methods among under-screened women in Flanders. Individual interviews with 15 underscreened women aged 30–64 years were conducted. During the interviews, participants were given the opportunity to try out a urine and vaginal self-sampling kit. Thematic analysis was based on Ajzen’s model of the Theory of Planned Behavior. The results showed that 14 out of 15 participants were more likely to participate in CCS if they had the option to self-sample. One of the main findings was a lack of knowledge on different aspects of cervical cancer. Most women had a positive attitude toward cancer screening and primary prevention such as HPV vaccination. Subjective norms were influenced by healthcare professionals, peers, and organized government initiatives. Informational, organizational, contextual, and emotional factors were mentioned as barriers as well as facilitators for participation. Additionally, high self-efficacy was considered to make self-sampling more convenient. All women showed the intention to use at least one method of self-sampling. We can conclude that women who do not participate in CCS would be more motivated to participate using self-sampling methods. Adequate education and guidance should be provided.